Human Body and Image: study of Anatomy in the 5th year of Elementary School through a didactic game (Research, Society and Development, 2022)
As highlighted in the literature, didactic games play an important role as motivating agents, leading students to assume a more active posture in the teaching-learning process and fostering the construction of knowledge in a dynamic way, as long as there is a balance between the playful and educational aspects. This article deals with the process of validation and evaluation of the didactic game "Human Body and Image" as an auxiliary tool in the study of Human Anatomy, by students of the 5th year of Elementary School of a public school in the city of Santo Antônio de Pádua-RJ. Two questionnaires were used for validation: the "Knowledge Survey" and the "Learning Verification", applied before and after the start of the game, respectively. For the evaluation of the didactic game, the questionnaire “Use of the Didactic Game” was applied. The data obtained indicate that the didactic game "Human Body and Image ” was well evaluated by the students participating in the research, suggesting that it can be used to approach contents related to Anatomy at the level of the 5th year of Elementary School.